Technologies for personalization of brand marketing communications using artificial intelligence - A. N. Timokhovich; O. S. Bulycheva (Цифровая социология)
The article deals with the problem of implementation of personalization in marketing communications based on empathy of brand consumers. The paper substantiates the significance of artificial intelligence in the collection and processing of a large amount of personal data of users of the online space. The article presents an analysis of the main scientific approaches of Russian and foreign authors specializing in the study of the emotional component in the construction of personalized online communications. The authors present the results of the comprehensive research of consumers’ attitude to the personalization of marketing communications based on the artificial intelligence capabilities. In the course of the study the authors consider the technologies of using artificial intelligence mechanisms in the construction of personal communications in the online environment. The article gives theoretical substantiation of the need to use the mechanism of empathy in the construction of personalized communication with consumers. The paper substantiates conclusions about the possibility to build empathic connection between brands and their consumers under the condition of activating the function of emotional contagion, the effectiveness of using the emotional state of consumers in the preparation of personalized offers. The study describes the specifics of using personalized marketing communications as a modern marketing tool, which is expressed in the impact on the identification of buyers at the subconscious level. The article presents the technologies of personalization through consumers’ attitudes towards personalized communications. The paper presents the results of an empirical study conducted by the authors of the article in the spring of 2020, aimed at determining the willingness of consumers to share information about their emotional states. The article makes the conclusions about the existence of consumers’ need for trusting relationship with brands based on the mechanism of empathy; about the possibility of increasing the effectiveness of personalized brand communications through the use of segmentation of consumers depending on their mood; about the benefits of using artificial intelligence technologies in marketing communications.